Factors Affecting Construction Labor Productivity In Peshawar Khyber Pakhtunkhwa (KPK) Pakistan - Shah, Syed Waqar Ali; Ahad, Muhammad Zeeshan (Advances in Social Sciences Research Journal, 2017)
Labor productivity is at forefront of concerns facing professionals in construction industry worldwide. Construction industries play a leading role in economic growth for countries all around the world. This study highlights the factors affecting labor productivity in the construction industry of Peshawar (Khyber-Pakhtunkhwa) Pakistan. Improvement in productivity results in saving of cost and time. This study explores various factors for improving labor productivity in construction industry of Peshawar. Questionnaire survey and practical productivity assessment was adopted to take out the effect each individual productivity factors. The relative importance index (RII) of all twenty three (23) factors affecting productivity was identified. This study also developed a comparison sheet with previous case study data conducted by authors Anu V.Thomas and J.Sudhakumar (India) which could be used by the project managers to easily sort out various factors related to productivity improvement in different regions. The major factors which sort out and outcomes of this study will help project managers to anticipate weak zones of productivity in their present projects and provide accurate strategies for improving labor productivity.